Accelerated radiotherapy with concomitant boost technique (69.5 Gy/5 weeks) : an alternative in the treatment of locally advanced head and neck cancer - Kubes, Jiri; Cvek, Jakub; Vondracek, Vladimir; Pala, Miloslav; Feltl, David (Strahlentherapie und Onkologie, 2011)
BACKGROUND AND PURPOSE: To present the feasibility and results of accelerated radiotherapy with concomitant boost technique (69.5 Gy/5 weeks) in the treatment of locally advanced head and neck cancer. PATIENTS AND METHODS: A total of 65 patients were treated between June 2006 and August 2009. The distribution of clinical stages was as follows: II 11%, III 23%, IV 61%, and not defined 5%. RESULTS: The median follow-up was 30.5 months. The treatment plan was completed in 94% of patients. Patients were treated using the conformal or intensity-modulated radiotherapy (IMRT) technique. The median overall treatment time was 37 days (13-45 days). The mean radiotherapy dose was 68.4 Gy (16-74 Gy). Overall survival was 69% after 2 years. Disease-free survival was 62% after 2 years. Acute toxicity ≥ grade 3(RTOG scale) included mucositis (grade 3: 42.6%), pharynx (grade 3: 42.3%), skin (grade 3: 9.5%), larynx (grade 3: 4%), while late toxicity affected skin (grade 3: 6.25%) and salivary glands (grade 3: 3.7%). CONCLUSION: Accelerated radiotherapy with concomitant boost technique is feasible in patients with locally advanced head and neck cancer, has an acceptable toxicity profile, and yields promising treatment results.
Keywords: dospělí; Nasopharyngeal Neoplasms; Female; Feasibility Studies; Adult; nádory nosohltanu; výsledek terapie; ženské pohlaví; Hypopharyngeal Neoplasms; přežití bez známek nemoci; Radiation Injuries; lidé; staging nádorů; Mouth Neoplasms; Otorhinolaryngologic Neoplasms; Treatment Outcome; nádory hypofaryngu; následné studie; Radiotherapy, Conformal; nádory úst; studie proveditelnosti; Follow-Up Studies; radiační poranění; Male; Aged; konformní radioterapie; Disease-Free Survival; lidé středního věku; senioři; mužské pohlaví; otorinolaryngologické nádory; radioterapie s modulovanou intenzitou; Radiotherapy, Intensity-Modulated; Middle Aged; Neoplasm Staging; Humans